Kajian Normatif Problematika Pemindahtanganan Barang Milik Daerah dengan Status Hak Pakai kepada Desa Adat - Kusuma Dewi, Komang Lestari; Astha, I Ketut Purna; Saputri, Ni Wayan Legi Sugiati (Jurnal Yustitia, 2023)
Regional property in the form of land must be certified in the name of the localgovernment, as in the registration of land rights for local governments in the form of usage rightsor management rights. After the issuance of Government Regulation Number 18 of 2021, landwith the status of usage rights cannot be transferred, especially usage rights for period of time aslong as they are used. The legal ratio for prohibition on the transfer of Regional Property becausethe limitations attached to usage rights owned by the local government are Public Use Rights withthe implication is only right to use not rights of disposal. So it is suggested for the management ofRegional Property by Traditional Villages it would be possible to use the mechanism for utilizationof Regional Property in accordance to the Laws and Regulations.